An Evaluation of Medical Record Keeping Status to Assess Health Care Facilities for Hospitalized Patients In A Tertiary Care Hospital - Ahmed, Gazi Ikhtiar; Zaman, Md Maruf Hasan; Kafi, Md Abdulla Hil; Islam, Nahidul; Rahman, Syed Atiqur (KYAMC Journal, 2022)
Background: A patient’s medical record should provide accurate information on who the patient is and who provided health care; what, when, why and how services were provided; and the outcome of care and treatment. Objectives: The study was conducted with the objective of revealing the condition of medical audit of the inpatient department in Rangpur medical college hospital in short duration of time. Materials and Methods: A cross-sectional descriptive study was done in inpatient department in Rangpur Medical College & Hospital. This was carried out on 160 medical documents, interview with providers, record of hospital statistics & personal observation on physical facilities in indoor at the time of the study to find out in what extend medical record exist in patient service. Results: In inpatient department of Hospital, the generation and location of the form in all wards were inpatient, administrative office & type of the forms were mixed pattern. There was no electronic record system in the medicine department. They consisted of forms, sheet & register khata. Medical records were not filled of in most of the cases. A hundred and sixty records were checked where most of the components were not filled up completely (above 30% not filled up). The recording of hospital statistics were satisfactory and maintained regularly in the inpatient department. Conclusion: The standard of documentation by providers in inpatient medical records was found to be acceptable, with improvements required in a number of specific items. KYAMC Journal Vol. 13, No. 02, July 2022: 81-85